2016
DOI: 10.2147/oaem.s69976
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to reduce the risk of violence toward emergency department staff: current approaches

Abstract: IntroductionThe phenomenon of workplace violence in health care settings, and especially in the emergency department (ED), has assumed the dimensions of a real epidemic. Many studies highlight the need for methods to ensure the safety of staff and propose interventions to address the problem.AimThe aim of this review was to propose a narrative of the current approaches to reduce workplace violence in the ED, with a particular focus on evaluating the effectiveness of emergency response programs.MethodsA search … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
72
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 58 publications
1
72
0
5
Order By: Relevance
“…Consistent with a previous study (Fasanya & Dada 2016), we found that 94.3% of the subjects who were psychologically traumatised still continued their work when they experienced WPV. According to a previous study, 88% of the sampled participants failed to report WPV because of fear of losing their jobs and inappropriate handling of the situation by management (Fasanya & Dada 2016), or due to the high prevalence of the belief of nurses that violence is an inevitable part of the job (Ramacciati et al 2016). However, we also found that those who had experienced all three types of violence suffered more severe secondary trauma than those who had not experienced any type of violence or one type of violence.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with a previous study (Fasanya & Dada 2016), we found that 94.3% of the subjects who were psychologically traumatised still continued their work when they experienced WPV. According to a previous study, 88% of the sampled participants failed to report WPV because of fear of losing their jobs and inappropriate handling of the situation by management (Fasanya & Dada 2016), or due to the high prevalence of the belief of nurses that violence is an inevitable part of the job (Ramacciati et al 2016). However, we also found that those who had experienced all three types of violence suffered more severe secondary trauma than those who had not experienced any type of violence or one type of violence.…”
Section: Discussionmentioning
confidence: 99%
“…We used the QuIN16VIPs Questionnaire as the survey instrument. This questionnaire was designed specifically for the study of violence towards Emergency nurses, starting from a comprehensive literature review and from selected studies based on surveys (Ramacciati, Ceccagnoli, Addey, Lumini, & Rasero, 2016). In addition to this, we followed best practices for surveys addressed to healthcare staff (McColl et al, 2001;Ramacciati, 2013).…”
Section: Instrumentsmentioning
confidence: 99%
“…The questionnaire resulted stable with K of Cohen-Fleiss equal to 0.71. Median compilation time was 14 min and 09 s with a range of 7 min, 50 s and 20 min, 00 s. The validation study of the questionnaire has been published(Ramacciati, Ceccagnoli, Addey, Lumini, et al, 2016).…”
mentioning
confidence: 99%
“…7 Table 1 shows the ED attendees, type of violence, perpetrator, incidence of WPV and the proportion of drug and alcohol affected patients among the ED WPV population for the year. 2 Of course, our findings may be related both to the small size of our sample and to the phenomenon of non-reporting; however, to date we have carried out three surveys (April 2013, November 2015 and March 2017) with the nursing staff concerning the reporting of violent events in the past year.…”
mentioning
confidence: 90%